Studi Literatur tentang Peran Media Sosial dalam Meningkatkan Kesadaran Bela Negara di Kalangan Generasi Z - Gozal, Angel Vallerie; Byanca, Zayra Alana; Beatitudo, Ewaldus Senarai; Surjo, Fernando Romero; Kasdim, Riska; Tumanggor, Raja Oloan (Lembaga Yasin AlSys, 2025)
Social media is a relevant thing for Generation Z, who has interacted with technology since birth. Generation Z has an important role in maintaining and strengthening Indonesia’s democracy, one of which is through state defense actions carried on social media. Generation Z’s active participant, such as voicing opinions, following the democratic process and fighting threats that could damage democracy, is a real form of defending the country in a digital context. Even though social media has a big influence in spreading the message of defending the country, the challenge faced is how to benefit from the social media carefully and wisely to filter the correct information. This research aims to determine the role of social media in increasing awareness of defending the country among generation Z. This research uses a literature study approach. The results of this research shows that social media has significant potential in increasing the awareness of defending the country among the younger generation, especially generation Z.